2001
DOI: 10.2134/jeq2001.302337x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Nitrogen in Surface Waters as Influenced by Climatic Conditions and Agricultural Practices

Abstract: Subsurface tile drainage from row-crop agricultural production systems has been identified as a major source of nitrate entering surface waters in the Mississippi River basin. Noncontrollable factors such as precipitation and mineralization of soil organic matter have a tremendous effect on drainage losses, nitrate concentrations, and nitrate loadings in subsurface drainage water. Cropping system and nutrient management inputs are controllable factors that have a varying influence on nitrate losses. Row crops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
340
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 421 publications
(361 citation statements)
references
References 11 publications
16
340
0
5
Order By: Relevance
“…Predicting N changes in rivers is particularly difficult because of the many 299 biological interactions it undergoes. Higher rates of N mineralization during the warmer drier 300 summers would result in a greater build-up of nitrogen in the soils (Randall and Mulla, 2001; 301 Whitehead et al, 2002), although this might be partially compensated by higher rates of plant 302 uptake. Actually, long-term records of streamwater quality have shown that dry summers 303 result in high rates of diffuse source nitrogen delivery when the drought breaks (Whitehead et 304 during the autumn and winter periods (Bouraoui et al, 2002 and autumn under both the low and high -emission scenarios (Tables 1 and 2).…”
mentioning
confidence: 99%
“…Predicting N changes in rivers is particularly difficult because of the many 299 biological interactions it undergoes. Higher rates of N mineralization during the warmer drier 300 summers would result in a greater build-up of nitrogen in the soils (Randall and Mulla, 2001; 301 Whitehead et al, 2002), although this might be partially compensated by higher rates of plant 302 uptake. Actually, long-term records of streamwater quality have shown that dry summers 303 result in high rates of diffuse source nitrogen delivery when the drought breaks (Whitehead et 304 during the autumn and winter periods (Bouraoui et al, 2002 and autumn under both the low and high -emission scenarios (Tables 1 and 2).…”
mentioning
confidence: 99%
“…However, previous studies have shown that the timing of fertilizer application and the amount of nitrogen applied are the main factors affecting it (Malone et al 2007). Thus, appropriate timing and optimal fertilizer rates are keys to reducing N losses from farmland (Randall and Mulla 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Measures to curb downward movement of N like timely application of inputs and split fertilizer application that have been reported to reduce leaching should be encouraged (Randall and Mulla, 2001). In addition trees if well planted and integrated in the farming systems may assist in recovering some of this N that is lost to annual crops as observed by Mugendi et al (2003) who reported that treatments with tree hedges recorded a lower amount of mineral N in the 100-300 cm depth than treatments without tree hedges.…”
Section: Discussionmentioning
confidence: 99%